Advantages and limitations of whole-body bone marrow MRI using turbo-STIR sequences in comparison to planar bone scans - Tausig, A.; Manthey, N.; Berger, F.; Sommer, H.; Pfluger, T.; Hahn, K. (Nuklearmedizin - NuclearMedicine, 2000)
At modern MRI tomographs the whole body can be screened for bone marrow metastases within 45 min. Aim of this study was to evaluate the diagnostic advantages and disadvantages of a whole-body bone marrow MRI protocol using Turbo Short Tau Inversion Recovery [STIR] sequences in comparison to planar bone scintigraphy (SZ). Patients and methods: In order to screen for bone metastases within two weeks SZ and whole-body MRI with Turbo-STIR-sequences were performed in 20 patients with known breast cancer. For further evaluation five regions were defined: scull, spine including the pelvis, femora, humeri and ribs including scapulae and sternum. Results: In 9/20 patients neither with SZ nor with MRI bone metastases were detected (staging M0). Among the remaining 11 patients SZ detected 109 and MRI 150 lesions which were typical for bone metastases. All of these 11 patients were staged Ml correspondingly with both methods. Within the thorax (ribs, sternum, scapulae) MRI discovered only 6/17 and within the scull 0/6 lesions which were suspicious for metastases in SZ. Inversely MRI identified much more metastatic lesions than SZ within the femora (20/16), the humeri (14/12) and the spine including the pelvis (110/58). Conclusions: Susceptibility-, truncation*, chemical-shift-, third arm- and particularly pulsation artifacts along with the impossibility to chose slice orientation equally advantageous for all regions of the body cause impaired image quality of MRI whole body scanning. Therefore, concerning the detection rate of bone metastases within the thorax (ribs, sternum and scapulae) and the scull, conventional Turbo-STIR-MRI whole-body scans are even less accurate than conventional planar bone scintigraphy in those regions.
Keywords: Whole body MRI; artifacts; bone scintigraphy; bone metastases; breast cancer